Generation of stable orthogonal gradients of chemical concentration and substrate stiffness in a microfluidic device1. Issue 12 (21st June 2015) - García, S.; Sunyer, R.; Olivares, A.; Noailly, J.; Atencia, J.; Trepat, X.
<x xml:space="preserve">Abstract</x> A microfluidic device that generates a stable, linear and diffusive chemical gradient over a biocompatible hydrogel with a stiffness gradient.